Close-to-nature silviculture in eastern Quebec: Advances over the last decade - Robert Schneider; Laurie Dupont-Leduc; Vincent Gauthray-Guyénet; Nicolas Cattaneo; LaraMelo; Tommy Simard; Alexis Begni; Raphel Turquin; Anabelle Morache-Mercier; Samuel Pinna; Ulysse Rémillard; Charles Nock (The Forestry Chronicle)
The increase in intensity of the harvesting of eastern Quebec’s forests has resulted in profound compositional changes at the stand level. The composition and structure of presettlement stands provide key benchmarks when implementing ecosystem-based management (EBM). A core principle of EBM is the emulation of natural disturbances, and it is hypothesized that forest resilience will be maintained. Managers have thus adapted some of their silvicultural activities to better mimic the main natural disturbances in eastern Quebec. These adaptations include using variable retention harvesting systems instead of clear-cuts and converting even-aged stands. Nevertheless, other close-to-nature silvicultural practices must be developed, as gaps between managed and unmanaged stands persist. Most importantly, there is a need to consider global change within EBM, which could be accomplished by prioritizing forest functions rather than composition or structure when establishing silvicultural objectives. Elements of the complex adaptive systems approach to increasing forest resilience can be incorporated into the larger-scale EBM approach. This could be done by considering the functional complementarity of species, forest function, and stand structure in forest management planning. These efforts must not be constrained, however, to allowable annual cut calculations, as these are not sufficiently sensitive to compare different management scenarios.